Join in! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Participatory Workshops. A Sourcebook of 21 Sets of Ideas & Activities By R Chambers, Earthscan Publications, London, 2002. 240 pp. ISBN 1 85383 863 2 GBP 8.95 Euro 14